A REVIEW ON CHITHIRAMOOLA KULIGAI – THERAPEUTIC APPROACH FOR CERVICAL CANCER IN ACCORDANCE WITH SIDDHA PRINCIPLES - Subathra T; Gomathi R; Shanmugapriya P; Ramamurthy M; Meenakumari R (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Cervical cancer remains a significant global health challenge, claiming millions of lives annually despite advancements in medical science. This paper explores the multifaceted landscape of cervical cancer treatment, examining both conventional approaches and the potential benefits of integrating Siddha medicine, a traditional Indian system, into cancer care. While conventional treatments like surgery, chemotherapy, and radiotherapy are effective, they often come with significant side effects. Siddha medicine offers a holistic perspective, focusing on restoring balance and addressing individual constitution. One notable Siddha remedy, Chithiramoola Kuligai (CMK), stands out for its historical efficacy in treating various ailments, including cervical cancer. This herbo-metallic compound, composed of Plumbago zeylanica, Tachyspermum ammi, Mercurous chloride, and Palm jaggery, demonstrates potential anti-cancer properties while mitigating treatment side effects. The paper underscores the importance of patient-centered care by highlighting the meticulous selection of raw drugs in formulating CMK based on Siddha basic principles to treat cervical cancer, thus integrating diverse therapeutic modalities to meet the complex needs of patients while emphasizing the promise of Siddha medicine in enhancing treatment outcomes and improving overall well-being.